The level of psychological stress responsible for school violence among secondary school students from the point of view of teachers (A field study) (Journal of Hama University, 2024)
The aim of the current research is to identify the level of psychological stress responsible for school violence among secondary school students from the point of view of teachers. And detecting the difference between the average scores of the sample members on a scale of psychological pressures responsible for school violence among secondary school students, according to the variables (gender, academic qualification, specialization). The research adopted the descriptive approach, and the research community included all secondary school teachers in schools in the city of Latakia, numbering (1684), where (310) questionnaires were distributed to the secondary school teachers, and /299/ complete questionnaires were retrieved from them, suitable for statistical analysis. The results showed that The most important psychological pressures responsible for school violence among secondary school students from the point of view of the teachers of the study sample is that family upbringing and parental treatment have the largest role and cause of the pressures responsible for violent behavior in children, and that school has the largest role and cause of the pressures responsible for violent behavior in children. the students. There are also no statistically significant differences at the significance level of 0.05 between the average scores of the sample members on a scale of the psychological pressures responsible for school violence among secondary school students, depending on the academic qualification variable. It was also found that there is a statistically significant difference at the significance level of 0.05 between the average scores of the sample members on a scale of the psychological pressures responsible for school violence among secondary school students due to the variables of gender and specialization
Keywords: psychological stress; school violence; secondary school